A Biodegradable Multifunctional Film as a Tissue Adhesive for Instant Hemostasis and Wound Closure. Issue 9 (5th May 2022) - Huang, Wen‐Can; He, Yongjun; Wang, Wei; Mao, Xiangzhao
Abstract : Front Cover : In article number 2200031 by Xingzhao Mao and co‐workers, a multifunctional film (MFF) as a tissue adhesive in the form of an interpenetrating network is developed. The MFF combines enhanced physical and antibacterial properties, allows facile and tough attachment to the wet and dynamic tissues and presents outstanding hemostasis and sealing properties.